Acesso e repartição de benefícios: a implementação do Protocolo de Nagoia no Brasil - Lima, João Emmanuel Cordeiro (2022)
The work investigates the measures that should be adopted by Brazil for the effective implementation of the The Nagoya Protocol on Access to Genetic Resources and the Fair and Equitable Sharing of Benefits Arising from their Utilization to the Convention on Biological Diversity (“Protocol”). To this end, it initially demonstrates the relevance of biodiversity, the risk of its loss and the role of adopting and implementing international environmental treaties for its protection, with emphasis on the Convention on Biological Diversity (CBD) and the Protocol. Next, the origin, structure and function of the mechanism for accessing genetic resources and associated traditional knowledge and the sharing of benefits arising from their use, conceived as an objective of the CBD and promoted by the Protocol, are studied. Subsequently, the general aspects of the Protocol are analyzed and the obligations that Brazil must comply with in order to implement this treaty are identified and detailed, dividing them into four groups: (i) obligations related to the regulation of prior informed consent to access to genetic resources and associated traditional knowledge; (ii) obligations related to the benefitsharing arising from access; (iii) obligations aimed at ensuring compliance with the foreign regulation of access and benefit sharing (compliance); and (iv) obligations related to the adoption of support measures aimed at the implementation of the treaty. Finally, we exame the legal nature of the accts that must be practiced for the implementation of the Protocol and its possible content, presenting, when relevant, suggestions for a more effective implementation